The Influence of Discount Vouchers and Free Shipping on the Frequency of Online Food Purchases among Students Using ShopeeFood at Universitas Negeri Jakarta - Azzahrani Hafshah Valiandri; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The objective of this study is to analyze the impact of discount vouchers plus shipping free on the frequency of online food and beverage purchases on the ShopeeFood platform with respondents from the Economics Faculty and Business Jakarta State University (FEB UNJ). This work employs a quantitative methodology using structural equation modeling based on partial Least Squares-Based. (SEM-PLS) method processed using SmartPLS. Questionnaires were used to gather data to FEB UNJ students who actively use ShopeeFood. The results show that discount vouchers and free shipping have a favorable and substantial impact on purchase frequency, with the influence of free shipping being more dominant. These findings indicate that promotional strategies focused on reducing transaction costs are effective in encouraging increased repeat purchases in the student segment.